REVIEW OF INDOOR RADON CONCENTRATIONS IN SCHOOLS AND KINDERGARTENS. Issue 1 (12th June 2018) - Zhukovsky, M; Vasilyev, A; Onishchenko, A; Yarmoshenko, I
Abstract: Analysis includes review of 63 national and regional indoor radon surveys in kindergartens and schools. Preliminary assessment of the worldwide population weighted characteristics of radon concentration in children's institutions is: arithmetic mean = 59 and geometric mean = 36 Bq/m 3 . Higher indoor radon concentrations in children's institutions in comparison with the dwellings can be explained by characteristics of ventilation, attendance regime and construction features. Special protocol of measurements in the kindergartens and schools is required.